Comparison of early versus late onset familial Mediterranean fever - (:unkn) unknown (WILEY, 2018)
AimFamilial Mediterranean fever (FMF) is the most common autoinflammatory disease. One of the common characteristics of this disease is its young age predominance. Nearly 90% of patients experience disease flares during early adult age periods. Currently there are limited data for the comparison of early versus late onset FMF and therefore the primary aim of this study was to investigate these two subsets with regard to their certain demographic, clinical and genetic differences. MethodsEarly (20years, Group 1) and late (>20years, Group 2) onset FMF patients were identified from the national FMF registry that involves 2246 patients from 15 adult rheumatology clinics located in different geographical areas of Turkey. ResultsOf the 2246 patients, 1633 (72.7%) were aged 20years old (Group 1) and the remaining 613 were older than 20years (Group 2). Delay in diagnosis was longer in Group 1 and fever, peritonitis, pleuritis, erysipelas-like erythema (ELE), arthritis, family history of FMF and amyloidosis were more common in Group 1. On the other hand, sex distribution, rates of amyloidosis, vasculitis and kidney failure were not different between the groups. Among patients with available genotypes, homozygous and heterozygous M694V mutations weresignificantly higher and heterozygous E148Q mutation was significantly lower in Group 1 compared to Group 2. ConclusionPatients with FMF whose symptoms start before 20years of age seem to have severe symptoms and M694V mutation may be responsible for the early expression of the disease.
Keywords: age at onset of disease; early onset; familial Mediterranean fever; M694V; TURKISH PATIENTS; TURKEY; MULTICENTER; AMYLOIDOSIS; FMF